The portfolio-focused management of ship-repair production - Шахов, Анатолий Валентинович; Шамов, Алексей Владимирович (Eastern-European Journal of Enterprise Technologies, 2012)
Worked out methodical bases of portfolio methods for the management of repair production. Also there were offer original methods of determination priorities of projects, formation of an effective portfolio’s projects, resource management of a portfolio on the basis of application GERT-networks.